PENGARUH EKSTRAKURIKULER PASKIBRA TERHADAP PENGAMALAN NILAI-NILAI NASIONALISME DI SMKN 4 PEKANBARU - Kurnia Wirawan; Hambali Hambali; Indra Primahardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on problems that often occur in the school environment, one of these problems is the fading of nationalist values. Among the factors that influence this is the process of globalization. Several studies say that there is a weakening or shallowing of Nationalism among the younger generation. Triatna (2013) said that in the current era of globalization, the spirit of nationalism among the younger generation is experiencing a decline. The weakening of the spirit of nationalism in the younger generation could be a risk of weakening the values ​​of patriotism which are the basis of our love for our beloved homeland. The aim of the research is to find out whether there is an influence of extracurricular activities on the practice of nationalist values ​​at SMKN 4 Pekanbaru. This research uses quantitative methods with a statistical approach. This research was conducted using observation, questionnaire and documentation methods. Based on the results of statistical data tests, it was obtained that Fhit ≥ Ftab, namely 78.013 ≥ 4.09, this means that the hypothesis in this study is accepted. Furthermore, the coefficient of determination value was 0.667. Based on these results, it can be concluded that the influence of Paskibra Extracurricular on the Practice of Nationalist Values ​​at SMKN 4 Pekanbaru is 66.7% at the "Strong" level.